Correlations Between the Perception of Family Violence and the Report of Violence in Students from São Paulo - Mariana Fernandes Prado Tortorelli; Luiz Renato Rodrigues Carreiro; Marcos Vinicius de Araújo (Psicologia, 2010)
Bullying is understood as a set of intentional repeated aggressive attitudes that characterize abuse of power of one student towards another. This work investigated correlations between the perception of family violence and the report of violence in elementary school students from São Paulo. 501 elementary school students from São Paulo responded to a questionnaire that consisted of six questions about family violence perception and seven questions related to the report of violence in school. Data was analyzed descriptively and a Pearson analyses was used to determine correlations between questions. Results demonstrated positive correlations between family violence perception and reports of violence in school. Family‑school relations is understood as interdependent and the school as a propitious place for dialogue aimed at preventing violence in both contexts (family and school). The purpose was not to blame one or another, but consider them as two institutions that can establish effective partnership to combat bullying.